2018
DOI: 10.1021/acs.organomet.8b00372
|View full text |Cite
|
Sign up to set email alerts
|

Si–N Heterodehydrocoupling with a Lanthanide Compound

Abstract: La{N(SiMe 3 ) 2 } 3 THF 2 ] (1) is an effective precatalyst for the heterodehydrocoupling of silanes and amines. Coupling of primary and secondary amines with aryl silanes was achieved with a loading of 0.8 mol % of [La{N(SiMe 3 ) 2 } 3 THF 2 ]. With primary amines, generation of tertiary and sometimes quaternary silamines was facile, often requiring only a few hours to reach completion, including new silamines Ph 3 Si( n PrNH) and Ph 3 Si( i PrNH). Secondary amines were also available for heterodehydrocouplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…A few metal-catalyzed cross-couplings of silanes and amines have been described . Recently, rare-earth metal complexes have also been demonstrated as highly efficient catalysts for the dehydrogenative coupling of hydrosilanes with amines . Modification of ligands have a great effect on the catalytic activity and selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…A few metal-catalyzed cross-couplings of silanes and amines have been described . Recently, rare-earth metal complexes have also been demonstrated as highly efficient catalysts for the dehydrogenative coupling of hydrosilanes with amines . Modification of ligands have a great effect on the catalytic activity and selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…SiÀN f-block catalysts used by Guan and Waterman. [56,57] catalysts, generally retain inferior reactivity.R eports of p-block catalysts are limited to ah andful of compounds, with several examples generally requiring forcingc onditions with an arrow substrate scope. Interestingly,m echanismsi nvestigated this far show significant similarity across the periodic table.…”
Section: Discussionmentioning
confidence: 99%
“…[56] Finally,W aterman showedt hat low loadings of the simple La[N(SiMe 3 ) 2 ] 3 (THF) 2 (32)could afford avariety of substituted silylaminesu sing primary,s econdary,a nd tertiarys ilanes with primary and secondary amines ( Figure 10). [57] Although forcing conditions such as excessa mine and heat were usually necessary to produce silylamines, product mixtures were not observedi nt his catalysis.…”
Section: F-block Catalystsmentioning
confidence: 99%
“…Recent work from Manners has demonstrated that tris­(pentafluorophenyl)­borane (BCF) can be used in conjunction with tertiary silanes at 100–130 °C to prepare phosphinosilanes along with elegant examples of cyclic phosphinosilanes when a primary or secondary silane is employed . Waterman has used La­[N­(SiMe 3 ) 2 ] 3 and a Zr catalyst for heterodehydrocoupling along with silylene elimination from silazanes, and Stephan has undertaken P–P bond activation to furnish phosphinosilanes using a Rh catalyst. , There are few examples of transition metal catalyzed dehydrocoupling methods for silylether formation, with examples in the literature being limited to late transition metals (likely due to oxophilicity in the early to midtransition metals). Ito and Sawamura have reported using Cu and Au, , while Yamada has tested a range of acetylacetonate (acac) salts, with Cu­(acac) 2 giving the highest yields (important to note is the very low reactivity obtained with Fe­(acac) 2 ) .…”
Section: Introductionmentioning
confidence: 99%